Caffeine Use: Association with Nicotine Use, Aggression, and Other Psychopathology in Psychiatric and Pediatric Outpatient Adolescents - Catherine A. Martin; Circe Cook; John H. Woodring; Gretchen Burkhardt; Greg Guenthner; Hatim A. Omar; Thomas H. Kelly (The Scientific World Journal)
The objective of this study was to evaluate the relationship between caffeine use, other drug use, and psychopathology in adolescents, using self-report measures. The study group consisted of 132 adolescents (average age 14.01 ± 2.06 years, 52% female, 19% African American, 5% other categories, 76% Caucasian). Most (47%) were recruited from a child psychiatry clinic with emphasis on youth with disruptive disorders, with 35% from an adolescent pediatric clinic with emphasis on prevention of risk-taking behavior and 18% from a pediatric clinic for families with limited resources. Subjects were consecutively recruited before or after regular clinic visits. Consent was obtained from parents and assent from the youth. High caffeine consumption was associated with daily cigarette use; aggressive behavior; conduct, attention deficit/hyperactivity, and social problems; and increased somatic complaints in adolescents.